Analisis Kualitas Fisik Tanah Pada Lahan Sawah Di Desa Bangkoor Kabupaten Sikka - Yovita Yasintha Bolly; Charly Mutiara (Agriculture Faculty of Flores University, 2023)
Bangkoor Village is one of the rice cultivation centers in Sikka Regency. Intensive agricultural activities supported by the availability of water sources allow farmers to cultivate rice three times a year. In addition, the use of various inputs such as the use of tractors, and the application of fertilizers and pesticides continues to increase crop productivity. On the other hand, the consequences of agricultural activities will certainly have an impact on the physical quality of the soil. This study aims to determine the physical quality of paddy soil in Bangkoor Village, Sikka Regency. The research method used is a survey method and analysis in the laboratory. Soil sampling using the purposive sampling method in three hamlets, namely Hamlet Mamai, Hamlet A, and Hamlet BC. Observational variables observed were soil texture, porosity, and soil water content. Assessment of soil quality using soil physical parameters. The results showed that some of the paddy fields in Bangkoor Village had been damaged or degraded by several factors, namely (1) the weight limiting factor for soil texture classes in the soil in Mamai hamlet, A hamlet, and BC hamlet. (2)The weight limiting factor for soil porosity in the soil BC sub-village.(3) The soil water content is included in the light-moderate limiting factor in all study locations. The effort that needs to be done is the addition of organic matter to paddy fields to be able to improve these limiting factors.